2016
DOI: 10.2174/1874210601610010619
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lingual Atrophic Conditions: Associations with Local and Systemic Factors. A Descriptive Review

Abstract: Atrophic glossitis is a condition characterised by absence of filiform or fungiform papillae on the dorsal surface of the tongue. Consequently, the ordinary texture and appearance of the dorsal tongue, determined by papillary protrusion, turns into a soft and smooth aspect.Throughout the years, many factors, both local and systemic, have been associated with atrophic glossitis as the tongue is currently considered to be a mirror of general health. Moreover, various tongue conditions were wrongly diagnosed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 112 publications
1
29
0
8
Order By: Relevance
“…Because of their lack of pain perception, patients are unconscious of these injuries and show no signs of discomfort. Also, one of the patients had limited mouth opening due to thick fibrous scar tissue in both the lips and the buccal mucosa, similar to previous reports (19,20) . Atrophic glossitis was seen in two of our patients as well as in previous studies (11,20,21) .…”
Section: Discussionsupporting
confidence: 88%
“…Because of their lack of pain perception, patients are unconscious of these injuries and show no signs of discomfort. Also, one of the patients had limited mouth opening due to thick fibrous scar tissue in both the lips and the buccal mucosa, similar to previous reports (19,20) . Atrophic glossitis was seen in two of our patients as well as in previous studies (11,20,21) .…”
Section: Discussionsupporting
confidence: 88%
“…In diabetes mellitus, candida infection in the oral cavity results in the formation of rhomboid glossitis. 44 This glossitis is marked by an erythematous tongue lesion anterior to the circumvallate papillae. The rhomboid-shaped lesion is found on the dorsal surface of the tongue along the midline, which is depapillated, having a shiny, smooth surface, and also referred to as a kissing lesion.…”
Section: Tongue Abnormalitiesmentioning
confidence: 99%
“… 42 Fissured tongue, atrophic glossitis, rhomboid glossitis, benign migratory glossitis are the abnormalities of the tongue suffered by diabetic patients. 23 , 43 , 44 diabetic individuals also suffer from Halitosis or bad breath, oral lichen planus, and oral lichenoid reaction ( Figure 1 ). 45–49
Figure 1 Complications of oral cavity in diabetes mellitus.
…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, it has been observed that tongue lesions were slightly predominant in females as compared to males. This could be because of hormonal changes, systemic alterations and nutritional imbalance among the female population [9]. These changes may primarily manifest in the oral cavity including the lingual surfaces [4].…”
Section: Discussionmentioning
confidence: 99%